Ponte miocárdica de artéria descendente anterior em ventrículo direito à angiotomografia das coronárias - Souto, Maria Júlia Silveira (2018)
Background: Myocardial bridging (MB) is defined as a segment of cardiac muscle overlying a great epicardial coronary artery, more commonly the Left Anterior Descending artery (LAD), and continues its path through the myocardium. The sort that crosses the right ventricular wall is hardly visualized by angiography, and has only been diagnosed in vivo after the implementation of the Coronary Computed Tomographic Angiography (CCTA). Thus, there are only few articles that describe this sort of myocardial bridging and its clinical characteristics. Objective: This study aimed to evaluate clinical and tomographic characteristics of patients diagnosed with left anterior descending artery myocardial bridging through the right ventricular wall. Methods: Descriptive and transversal study in which patients diagnosed with left anterior descending artery myocardial bridging were evaluated by CCTA. The clinical data and prior cardiac exams were obtained by the revision of standardized files, completed previously the realization of the CCTA. Results: A total of 1452 CCTAs were realized in the period of the study, of which 70 patients (4.8%) were diagnosed with left anterior descending artery myocardial bridging. The patients were divided in two groups: 19 (27.1%) patients that had MB through the right ventricular wall; and 51 (72.9%) patients that had MB through the septum or the left ventricular wall. The former presented younger patients (average age of 52.9 years old). 52.7% of the patients with MB through the right ventricular wall had symptoms compatible to coronary artery disease, and 66.7% of those who were submitted to functional cardiac tests were positive to myocardium ischemia. Besides, 6 patients with MB through the right ventricular wall realized a coronary angiography, but only 1 of them showed luminal reduction of the segment of LAD evolved and was not able to diagnose its etiology Conclusion: We observed MB through the right ventricular wall in 27.1% of the patients with myocardial bridging. These patients were mostly symptomatic and had a prior positive cardiac functional test for myocardium ischemia. In the group of patients that realized coronary angiography, only one showed the luminal reduction of the artery. This study demonstrates that this pathology is able to represent a parcel of patients with clinical symptoms of coronary artery disease, and the diagnoses isn’t possible through other imaging methods.